Irregular behaviours of coda /M/ in Tamil reduplications - Mohana Dass Ramasamy, (Penerbit Universiti Kebangsaan Malaysia, 2020)
In Reduplication, the Base and Reduplicant usually undergo various phonological changes to reconcile and harmonise them. Despite this general view, not many studies have attested to credibility of a single phoneme for its capacity of triggering various reactions, otherwise known as the emergence of the unmarked (TETU). A specific coda of such nature, bilabial /m/, in one of the Dravidian language Tamil is known for registering irregular reactions at the juncture of Base and Reduplicants, forcing the coda to trigger seven types of phonological reactions, a phenomenon that probably hard to witness in universal grammar. This study discusses the phonological and morphological reactions of reduplicative words as the consequences of TETU, which were resolved in language-specific ways, within Optimality Theoretic parameters. The results verify that as long as the conflicting markedness constraints do not interrupt reconciliation of reduplicative words in Tamil, the reconciliations take place systematically without markedness reduction or increase in reduplicant, except in reduplicative words ending with labial /m/. The reduplicants tend to reduce markedness of its prosodically weak position in many ways, while the same markedness is tolerated within the base words, in isolation or otherwise. It responds, at least, in seven different ways (in isolation or simultaneously) in reduplications, suggesting that the markedness reducing and markedness increasing should be addressed as a context-sensitive issue of reduplicant-base, in the lights of natural and prosodic phonology, collectively, but not in the absence of one against another, at least for the sensitive phonemic coda, like /m/, in hand.